Optimization of photoproduction of hydrogen by the bacterium Rhodobacter capsulatus: role of Pyruvate Formate Lyase - Sultana, Sadequa (BRAC University, 2012)
This thesis is submitted in a partial fulfillment of the requirements for the degree of Masters of Science in Biotechnology, 2010.